2007
DOI: 10.1161/circulationaha.107.706887
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutation in the HCN4 Cardiac Ion Channel Pore Affecting Synthesis, Trafficking, and Functional Expression Is Associated With Familial Asymptomatic Sinus Bradycardia

Abstract: Background-The hyperpolarization-activated nucleotide-gated channel-HCN4 plays a major role in the diastolic depolarization of sinus atrial node cells. Mutant HCN4 channels have been found to be associated with inherited sinus bradycardia. Methods and Results-Sixteen members of a family with sinus bradycardia were evaluated. Evaluation included a clinical questionnaire, 12-lead ECGs, Holter monitoring, echocardiography, and treadmill exercise testing. Eight family members (5 males) were classified as affected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 29 publications
4
116
0
3
Order By: Relevance
“…In particular, the role of HCN channels as the dominant mechanism in heart rate regulation has repeatedly been called into question (4,23). Human genetic studies have suggested that HCN4 channels are important components of the SAN pacemaker machinery (9)(10)(11)(12). A contribution of I f to heart rate determination is further supported by the observation of a heart rate-lowering effect in both humans and rodents when I f is specifically blocked with IVA (13,14,24).…”
Section: Hhcn4 -573x Expression Eliminates Camp Sensitivity Of If Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the role of HCN channels as the dominant mechanism in heart rate regulation has repeatedly been called into question (4,23). Human genetic studies have suggested that HCN4 channels are important components of the SAN pacemaker machinery (9)(10)(11)(12). A contribution of I f to heart rate determination is further supported by the observation of a heart rate-lowering effect in both humans and rodents when I f is specifically blocked with IVA (13,14,24).…”
Section: Hhcn4 -573x Expression Eliminates Camp Sensitivity Of If Andmentioning
confidence: 99%
“…Although these biophysical properties seem to make f-channels ideal molecular targets for heart rate regulation, the contribution of the major I f -mediating cardiac isoforms HCN2 and HCN4 to SAN function remains highly controversial. Although human genetic (9)(10)(11)(12) and pharmacologic (5,13,14) studies suggest a significant role for HCN4 subunits in SAN pacemaking in humans and rodents, recent data from transgenic mouse models have challenged this view (15,16). Targeted deletion of HCN4 in adult mice was found to cause heart ratedependent sinus pauses but to have no effect on either basal or maximal heart rate or heart rate regulation (16).…”
mentioning
confidence: 99%
“…Together, the loss-offunction effects of the shifts in the voltage dependence of 1795insD 41 ± 1** 70 ± 1** 124 ± 3** 54 47 ± 1 77 ± 2 141 ± 3 40 Van den Berg et al [12] In HCN4 G480R 32 ± 8* 49 ± 12* 101 ± 21* 7 55 ± 9 73 ± 11 126 ± 17 8 Nof et al [13] A485V 37 ± 3* 58 ± 6* 117 ± 27 14 49 ± 11 77 ± 12 140 ± 33 5 Laish-Farkash et al [14] 695X 36 ± 6* 56 ± 5* 131 ± 17 7 47 ± 6 72 ± 10 157 ± 26 6 Schweizer et al [15] Minimum (Min), average (Avg), and maximum (Max) heart rate (HR) obtained with 24-hour Holter recording. Data are mean ± SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Holter recording in 1795insD patients revealed sinus bradycardia with an ≈11% decrease in minimum, average, and maximum heart rate [12], as detailed in Table 1, which also shows the bradycardic effect of some typical HCN4 mutations [13][14][15] for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Increased I f current activity may lead to an increase in myocardial tissue self-perpetuation, which commonly results in a tachyarrhythmia. The molecular propagators of the I f current are hyperpolarization-activated cyclic nucleotide-gated (HCN) channels (11). Therefore, the inhibition of HCN channels has become a focus of study for the treatment of arrhythmia (6).…”
Section: Introductionmentioning
confidence: 99%